Health information-seeking on Reddit, by people who use opioids - Margaret Sullivan; Jonah Hancock; George Shaw; Chaoqun Ni (Information Research: An International Electronic Journal)
Introduction. In the most recent year that data is available, 101,035 people died from drug overdoses in the United States. For people who use drugs, obtaining treatment remains a significant barrier due to issues of fear, stigmatisation, and illegality. Some people turn to the anonymous social media site, Reddit, for obtaining health and harm reduction information.